A Simple Conceptual Model for the Self‐Sustained Multidecadal AMOC Variability - X. Wei; R. Zhang (Geophysical Research Letters, 2022)
Abstract Multidecadal variability of Atlantic Meridional Overturning Circulation (AMOC) has been reconstructed by various proxies, simulated in climate models, and linked to multidecadal Arctic salinity variability. Here we construct a simple conceptual model to understand the two‐way interactions of the Arctic with multidecadal AMOC variability through a delayed oscillator mechanism. We revise Stommel's Two‐Box Model by including an advective time delay for the Arctic density/salinity anomalies to reach the subpolar North Atlantic and a coupled negative feedback between the AMOC and the freshwater flux entering the Arctic through atmosphere and/or sea ice responses. Self‐sustained multidecadal AMOC oscillations exist in the revised Stommel's Two‐Box model if the oceanic advective time delay is longer than the oscillation threshold, and the periods of the AMOC delayed oscillator depend crucially on this advective time delay. The coupled freshwater feedback provides additional delayed negative feedback and reduces the advective time delay threshold required for the oscillations.